Synthesis, Characterization of Ceftibuten-Copper(II) Complex and Prediction of Its Biological Activity - Dey, Shuchismita; Zakir Sultan, Md.; Abdus Salam, Md. (Asian Journal of Chemistry, 2020)
Ceftibuten dihydrate, one of the third-generation cephalosporin antibiotic is effectively used in curing several infectious diseases. The complexation of drug with metal may enhance the antibacterial activity. In this work, a new complex of ceftibuten dihydrate with Cu(II) was synthesized, characterized and antibacterial activity is reported. The in vitro test showed that the antibacterial activity of complex of ceftibuten was greatly enhanced against Staphylococcus aureus and Salmonella typhi.